Simultaneous Detection of Escherichia coli and Agrobacterium tumefaciens by Using Gold Nanoparticle Enhanced Polymerase Chain Reaction - Xinyi Zhao; Baljit Singh; Christine O’Connor; Hugh J. Byrne; Furong Tian (Micro)
Escherichia coli (E. coli) and Agrobacterium tumefaciens (A. tumefaciens) are bacterial species commonly found in the environment, and they can do much harm to humans, animals and plants. As a result, it is necessary to find an accurate, rapid, simple method to detect the concentrations of them, and polymerase chain reaction (PCR) is one of the most suitable candidates. In this study, a gold nanoparticles (GNPs) enhanced polymerase chain reaction was developed, to simultaneously target the specific genes, 16S rDNA of E. coli and Tms1 of A. tumefaciens. PCR amplification times (CT values) of E. coli and A. tumefaciens were seen to be lowered significantly by the incorporation of GNPs. The fluorescence intensities in quantitative PCR amplifications of both E. coli and A. tumefaciens reached the maximum after around 40 cycles, and the PCR yield (maximum fluorescence intensity) was proportional to the maximum absorbance at 495 nm in the corresponding UV-vis spectra. GNPs were found to enhance the PCR yield of both E. coli and A. tumefaciens, and smaller sized GNPs (average 13 nm) showed a better enhancement effect compared to larger sized GNPs (average 30 nm). Conventional PCR showed that both E. coli and A. tumefaciens could be detected together with limit of detection of 10 CFU/mL for each bacterium, using GNPs of 13 nm. The results of this study could lead to improvement of multiplex PCR that can detect different bacteria species simultaneously.